FISCAL SYSTEM OF THE REPUBLIC OF SERBIA IN THE EU ACCESSION PROCESS - Lovre, Ivan K; Jotić, Jelena V (International Journal of Economic Practice and Policy, 2014)
Differences in the fiscal system and the elements of certain taxes in the EU member states, countries- pretenders and candidate countries, lead to the barriers to the free movement of factors of production and transport. This leads to fiscally induced distortion, while reducing the efficient allocation of resources, and resulting in the fragmentation of the market and the different forms of economic inefficiency. Analysis of the different paths of fiscal integration on which the European Union relies, points to a controversy in the ways of fiscal integration. On the one hand, tax neutrality and efficiency require a high degree of fiscal harmonization and on the other hand, the principle of subsidiarity means that each member state retains independence in taxation, and is therefore entitled to fiscal competition. The fiscal system of Serbia is very diversified and complicated, and requires further simplification of the tax system and reduction of the large number of fiscal instruments and a greater degree of decentralization in accordance with the principle of subsidiarity, proclaimed in the European Union.
Keywords: the fiscal system; fiscal harmonization; fiscal policy; the European Union; fiscal competition; integration; the principle of subsidiarity